What people believe about monetary finance and what we can('t) do about it: Evidence from a large-scale, multi-country survey experiment - Cars H. Hommes; Julien Pinter; Isabelle Salle (Bank of Canada, 2023)
We conduct an experiment within a large-scale household survey on public finance in France, the Netherlands and Italy. We elicit prior beliefs via open-ended questions and introduce a measure of macroeconomic policy literacy. An educational blog post from a central bank (CB) that opposes monetary-financed policies preceded by a short video on public finance can induce less support for monetary-financed proposals and more support for fiscal discipline and CB independence, no matter the respondent's level of literacy. However, prior beliefs matter, and contradictory information may be polarizing. Information affects the respondents' views by shifting their inflation and tax expectations associated to these policies.
Keywords: E70; E60; E62; E58; G53; H31; C83; 330; Central bank research; Fiscal policy; Monetary policy